ESTUDIO QUIMICO DEL AGAVE - OROZCO D, FERNANDO; MADINAVEITA, ANTONIO (Rockefeller Foundation, CD MEXICO, DF, MEX, 1854)
The author describes the development of public health facilities in Mexico The basic organization of the Federal Dept of Health is diagrammatically presented and a discussion given of the advancements that have been made since 1917
REVISTA DE LA SOCIEDAD MEXICANA DE HISTORIA NATURAL
Keywords: ESTUDIO QUIMICO, AGAVE; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; TAXONIMIA ANIMAL BIOQUIMICA